Regenerative cell injection in denervated muscle reduces atrophy and enhances recovery following nerve repair. Issue 5 (16th March 2013) - Schaakxs, Dominique; Kalbermatten, Daniel F.; Raffoul, Wassim; Wiberg, Mikael; Kingham, Paul J.
<x xml:space="preserve">Abstract</x> Introduction: Functional muscle recovery after peripheral nerve injury is far from optimal, partly due to atrophy of the muscle arising from prolonged denervation. We hypothesized that injecting regenerative cells into denervated muscle would reduce this atrophy. Methods: A rat sciatic nerve lesion was performed, and Schwann cells or adipose‐derived stem cells, untreated or induced to a "Schwann‐cell–like" phenotype (dASC), were injected into the gastrocnemius muscle. Nerves were either repaired immediately or capped to prevent muscle reinnervation. One month later, functionality was measured using a walking track test, and muscle atrophy was assessed by examining muscle weight and histology. Results: Schwann cells and dASC groups showed significantly better scores on functional tests when compared with injections of growth medium alone. Muscle weight and histology were also significantly improved in these groups. Conclusion: Cell injections may reduce muscle atrophy and could benefit nerve injury patients. Muscle Nerve 47: 691–701, 2013